Social position and economic system justification in Canada: Implications for advancing health equity and social justice from an exploratory study of factors shaping economic system justification - Card, Kiffer G.; Hepburn, Kirk (Frontiers in Public Health, 2022)
Objective. Many socio-economic reforms that could reduce health disparities are not implemented because people justify existing systems and fear changes thereto. This study aimed to identify socio-demographic factors associated with system justifying beliefs to better understand how they are maintained in Canada. In doing so, we hypothesized that (1) systems justification is a default cognitive position, buttressed by the palliative benefits of system-justification, (2) lack of success in a given system generally motivates people to doubt the legitimacy of that system, and (3) system-justifying beliefs are rejected only when the costs of doing so are low enough and/or the benefits are high enough to outweigh the innate needs-fulfilment benefits of system-justification. Methods. Testing these hypotheses, we recruited participants living in Canada, aged 16+, to complete an online survey after being recruited via paid social media advertisements. Multivariable regression models identified factors associated with Economic System Justification Scale (ESJS) scores. Explanatory variables included demographic measures of social position, self-rated health, and patterns of social inclusion. Results. Among 2,619 participants, system-justifying beliefs were wide-spread, with the average level of support across ESJS scale items exceeding 50%. Lower ESJS scores were associated with worse health, more loneliness, and lower socioeconomic status. Despite the pattern that marginalization erodes system-justification, several historically marginalized characteristics (e.g., non-white ethnicity and non-binary gender) were associated with relatively high system-justification, compared to matching privileged characteristics (e.g., white ethnicity; masculine gender). Conclusion. Supporting our hypotheses, we identify a general trend that social marginalization is associated with less system-justification. Those benefitting from the status quo (e.g., healthier, wealthier, less lonely) were more likely to hold system-justifying beliefs. However, some groups who are disadvantaged within the existing system reported higher system-justification – suggesting that system oppression may be a key moderator of the effect of social position on system justification.